2014
DOI: 10.1681/asn.2013010103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paricalcitol on Left Ventricular Mass and Function in CKD—The OPERA Trial

Abstract: Vitamin D seems to protect against cardiovascular disease, but the reported effects of vitamin D on patient outcomes in CKD are controversial. We conducted a prospective, double blind, randomized, placebocontrolled trial to determine whether oral activated vitamin D reduces left ventricular (LV) mass in patients with stages 3-5 CKD with LV hypertrophy. Subjects with echocardiographic criteria of LV hypertrophy were randomly assigned to receive either oral paricalcitol (1 mg) one time daily (n=30) or matching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 50 publications
3
192
2
6
Order By: Relevance
“…96 Small clinical studies in hemodialysis patients have demonstrated a role of vitamin D agonists in reducing left ventricular wall thickness and improving diastolic function parameters, although larger randomized trials in CKD have not. 97,98 These larger trials have suggested that activated forms of vitamin D reduce left atrial size and potentially episodes of heart failure, 97 which are interesting findings that warrant confirmation.…”
Section: Vitamin Dmentioning
confidence: 98%
“…96 Small clinical studies in hemodialysis patients have demonstrated a role of vitamin D agonists in reducing left ventricular wall thickness and improving diastolic function parameters, although larger randomized trials in CKD have not. 97,98 These larger trials have suggested that activated forms of vitamin D reduce left atrial size and potentially episodes of heart failure, 97 which are interesting findings that warrant confirmation.…”
Section: Vitamin Dmentioning
confidence: 98%
“…The long-term consequence of this increase with respect to cardiovascular risk has not been explored, but strong evidence relating higher FGF23 with worse outcome possibly cautions against excessive active vitamin D use. Indeed, although observational studies of hemodialysis patients suggest a survival advantage with active vitamin D therapy (111) (albeit attenuated at high doses) (112) and studies in non-CKD animal models attest to the protective properties of vitamin D receptor agonists (VDRAs) on cardiac hypertrophy (113,114), recent randomized controlled trials in CKD patients have failed to show any improvement in left ventricular structure or function with paracalcitol versus placebo (115,116). Thus, in the setting of CKD, the benefit of VDRAs on the heart seems uncertain.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Treatment with active vitamin D has been considered a key therapy for cardiovascular events in CKD,8 but controversy remains as beneficial effects on cardiac abnormalities as observed in animal models9 could not be confirmed in clinical trials 10, 11. Moreover, while in vitro studies suggested a protective role for vitamin D in ameliorating damaged endothelium,12, 13 experimental in vivo CKD studies have primarily focused on the prevention of vascular calcification of the medial layer and heart failure9, 14, 15 but paid little attention to structural endothelial damage.…”
Section: Introductionmentioning
confidence: 99%